Analysis of caesarean sections according to Robson’s criteria at a tertiary care teaching hospital in central India - Wahane, Aparna; Ghaisas, Ashwini S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The rate of caesarean section (CS) has been skyrocketed globally over the past three decades which makes it utmost essential to be reanalyzed. Hence, the Robson’s classification of international standards has become a need of an hour. This study aimed to analyze the trend of caesarean sections at a tertiary care teaching hospital, by using Robson’s criteria. Methods: This cross-sectional observational study was conducted at Government Medical College in Akola. The data was collected for the women delivered by CS during November 2017 to April 2019 and proportions in various groups as per Robson’s criteria were calculated. Results: The overall CS rate for the study period at our hospital was 63.89%. Robson Group 1 (24.5%) had the greatest representation in the study population followed by Group 5 (21.27%) and 3 (14.18%). While Groups 6 (10.13%) and 9 (0.63%) had the least representation. Group 5 was found to be the highest absolute contributor (20.5%) to overall CS rates followed by Group 1 (16.08%). Group 9 had a least possible share in the study population, but it had 100% CS rate. Conclusions: Robson’s classification must be implemented in all delivery units to avoid unnecessary caesarean sections. Every effort should be made to provide caesarean sections to women in need, rather than striving to achieve a specific rate and Robson’s criteria is a step forward in the same direction.